ANALYSIS OF THE MAIN CHARACTERS IN STORYLINE THE FILM “NANTI KITA CERITA TENTANG HARI INI” - muji Endah palupi; sri arfani (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2023)
The purpose of this study is to Analyze of The Main characters in Storyline The Film "Nanti Kita Cerita Tentang Hari Ini" directed by Angga Dwimas Sasongko. Before collecting data, first watched movies and read novels. This research method is descriptive qualitative. This film was adapted from novel by Marcella Febritrisia Putri. The first Indonesian to reach 2 million viewers in 2020. Film has won various awards. Storyline of this film tells the story of a family trying to maintain understanding and harmony. Conflicts in family are caused by in the past secrets that have not been revealed. This 121-minute film tells the story of a family of five, parents and three children. In my opinion interesting characters in this film are Narendra as father and Awan as youngest child. Narendra's character has endured traumatic feelings for years, making him seem overly possessive and indulgent to Awan, but on the other hand, Awan's character is actually disrespectful to her parents. Therefore, I conducted an analysis of two main characters. The approach is a literary study that has a big role for readers in accepting, experiencing and understanding literary works.